2012
DOI: 10.4208/cicp.151210.140711a
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Boltzmann Finite Volume Formulation with Improved Stability

Abstract: AbstractThe most severe limitation of the standard Lattice Boltzmann Method is the use of uniform Cartesian grids especially when there is a need for high resolutions near the body or the walls. Among the recent advances in lattice Boltzmann research to handle complex geometries, a particularly remarkable option is represented by changing the solution procedure from the original “stream and collide” to a finite volume technique. However, most of the presented schemes have stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 37 publications
0
17
0
1
Order By: Relevance
“…A coupled LB-FV method also has been adopted for different physical processes. For example, Zarghami et al (2012) developed a cell-centered FV method for discretizing the SRT to improve the stability of the fl ow fi elds over a range of Reynolds numbers (Re). More recently, coupled LB-FV methods have been developed for reactive transport processes for multiphysics problems.…”
Section: Coupled Lbm-dns For Multicomponent Reactive Transport Processesmentioning
confidence: 99%
“…A coupled LB-FV method also has been adopted for different physical processes. For example, Zarghami et al (2012) developed a cell-centered FV method for discretizing the SRT to improve the stability of the fl ow fi elds over a range of Reynolds numbers (Re). More recently, coupled LB-FV methods have been developed for reactive transport processes for multiphysics problems.…”
Section: Coupled Lbm-dns For Multicomponent Reactive Transport Processesmentioning
confidence: 99%
“…Outra vantagem com a utilização do LBMé a possibilidade de implementá-lo utilizando processos de paralelização [16,17], que agilizam a obtenção de resultados. Além disso,é um método que pode ser facilmente acoplado a outros métodos numéricos dependendo da necessidade apresentada no problema físico [15,18,19] e, dessa forma, possibilita-se a obtenção de resultados mais precisos do que se obteria com a utilização de apenas uma abordagem numérica. Tais acoplamentos também são vantajosos quando a referênciaé a hemodinâmica, justamente por se saber que o sangueé compostos por diversas partículas estruturalmente diferentes [6], além da necessidade de se modelar as paredes dos vasos por onde o fluxo sanguíneo percorre e a musculatura ao redor desses vasos.…”
Section: Introductionunclassified
“…This partially explains the lower drag coefficients that were obtained, since our 200D × 200D domain is much larger than that for all the other results presented. In fact, Zarghami et al (2012) use the smallest domain height, 16D, and obtain a much larger drag coefficient for Re = 20.…”
Section: Circular Cylinder In a Free Streammentioning
confidence: 99%
“…They concluded that their method showed better numerical stability than the central scheme. Zarghami, Maghrebi, Ghasemi, and Ubertini (2012) also use a cellcentered formulation, and address the stability issue by introducing upwind second order pressure-based biasing factors and artificial damping in the flux calculations.…”
Section: Intrdouctionmentioning
confidence: 99%
See 1 more Smart Citation